Analisis Pembiayaan Mudharabah Bank Pembiayaan Rakyat Syariah Terhadap Nonperforming Financing di Indonesia Tahun 2015-2020 - andiman, andiman; Widardjono, Agus (Institut Agama Islam Bengkulu, 2021)
This study aims to analyze the effect of the type of financing on the Non-Performing Financing (NPF) of Islamic People's Financing Banks in Indonesia for the 2015-2019 period. The research method used is panel data regression with the Fixed Effect model as the recommended model based on the results of the model selection test. The results showed that the Log Mudharabah variable had a negative effect on the Non Performing Financing of Islamic Rural Banks. Mudharabah Log, Non Performing Financing